THE EFFECT OF THE COOPERATIVE LEARNING MODEL TYPE NUMBERED HEADS TOGETHER (NHT) TO IMPROVE CRITICAL THINKING SKILL ON ECOLOGY AND BIODIVERSITY MATERIAL GRADE VII SMP - Isfahani Isfahani; Wina Dyah Puspita Sari (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study aims to determine the effect of the Numbered Heads Together (NHT) cooperative learning model on students learning outcomes and critical thinking skills in Ecology and Biodiversity material for Grade VII students at SMP Negeri 35 Medan. The research employed a quasi-experimental method using a nonequivalent control group design involving two classes with a total of 64 students, in which the experimental class was taught using the NHT learning model while the control class was taught using a conventional teacher-centered learning model. Data were collected through pretest and posttest instruments, and the improvement in students’ learning outcomes was measured using the normalized gain (N-Gain). The results showed that both classes experienced improvement; however, the experimental class demonstrated a higher increase, with an average N-Gain score of 0.523 categorized as medium, compared to 0.372 in the control class, which was also categorized as medium. Furthermore, the results of the onetailed independent sample t-test showed a significance value of 0.000 (p < 0.05), indicating that the improvement in learning outcomes of students taught using the NHT learning model was significantly higher than that of students taught using the conventional learning model. These findings indicate that the Numbered Heads Together (NHT) learning model has a positive and significant effect on students learning outcomes and can be used as an effective alternative model in science learning, particularly in Ecology and Biodiversity topics. ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran kooperatif Numbered Heads Together (NHT) terhadap hasil belajar dan kemampuan berpikir kritis siswa pada materi Ekologi dan Keanekaragaman Hayati kelas VII di SMP Negeri 35 Medan. Penelitian ini menggunakan metode kuasi eksperimen dengan desain nonequivalent control group yang melibatkan dua kelas dengan jumlah keseluruhan 64 siswa, di mana kelas eksperimen diajar menggunakan model pembelajaran NHT sedangkan kelas kontrol diajar menggunakan model pembelajaran konvensional yang berpusat pada guru. Pengumpulan data dilakukan melalui instrumen pretest dan posttest, sedangkan peningkatan hasil belajar siswa dianalisis menggunakan normalized gain (N-Gain). Hasil penelitian menunjukkan bahwa kedua kelas mengalami peningkatan hasil belajar, namun peningkatan pada kelas eksperimen lebih tinggi dibandingkan kelas kontrol, dengan nilai rata-rata N-Gain sebesar 0,523 pada kategori sedang, sedangkan kelas kontrol memperoleh nilai rata-rata N-Gain sebesar 0,372 yang juga termasuk kategori sedang. Selanjutnya, hasil uji independent sample t-test satu arah menunjukkan nilai signifikansi sebesar 0,000 (p < 0,05), yang menunjukkan bahwa peningkatan hasil belajar siswa yang diajar menggunakan model pembelajaran NHT secara signifikan lebih tinggi dibandingkan dengan siswa yang diajar menggunakan model pembelajaran konvensional. Berdasarkan hasil tersebut, dapat disimpulkan bahwa model pembelajaran Numbered Heads Together (NHT) berpengaruh positif dan signifikan terhadap hasil belajar siswa serta dapat digunakan sebagai alternatif model pembelajaran yang efektif dalam pembelajaran IPA, khususnya pada materi Ekologi dan Keanekaragaman Hayati.